The tenant phenomenon in intermediate cities: actors, values and tenant supply in the metropolitan area of Mendoza, Argentina (2023)
The rapid growth of tenant households in the main cities of Latin America has gone hand in hand with the decrease in owner households since the late 1990s. It is observed that the tenant households are condensed in the central areas of the cities where there has been a process of urban densification and there is greater sedimentation of the housing supply. In the Metropolitan Area of Mendoza (AMM), constituted as an agglomerate of intermediate size, this phenomenon called “tenancy process” is also reproduced. The territorial configuration of urban expansion is expressed in the “commodification” of the city, due to the valuation and conversion of urban land, into a real estate and financial business in which housing is a commodity and its accessibility is associated with purchasing power. of each home. The tenant reality of the AMM is analysed, based on the population growth between census periods, and the distribution in the urban territory. The tenancy phenomenon is analysed by the level of socio-housing vulnerability of tenant households on the relationship between rental values and income of the population. The methodology is inductive-explanatory, and combines documentary analysis techniques from primary and secondary sources, interviews, and quantitative measurement processes. The data is built by own consultation, census information and local real estate portals. As a result, it was obtained that the central departments of the AMM are mostly affected by the tenancy process and a greater degree of vulnerability.